Att tala för missionen: Bildspråk och retoriska strategier i Evangeliska Fosterlands-Stiftelsens Missionsskrifter 1897–1921 - Hedberg, Andreas (Tidskrift för litteraturvetenskap, 2016)
To Speak for the Mission: Metaphors and Rhetorical Strategies in Mission Booklets Published by Evangeliska Fosterlands-Stiftelsen 1897–1921 This paper analyzes metaphors and rhetorical patterns in mission booklets published by, and circulated within, Evangeliska Fosterlands-Stiftelsen, a missionary movement that was (and remains) a part of Svenska kyrkan (known until recently as the Lutheran Church of Sweden). The booklets were an attempt to promote Lutheran missions in East Africa, Central India and among sailors. This paper focuses on booklets concerned with the mission in India, and examines different forms of argumentation present in these publications, using the terms ethos, pathos and logos, the three modes of persuasion discussed by Aristotle. The booklets rely heavily on pathos, especially when dealing with the day-to-day work of the missionaries, while logos is mainly reserved for presenting the mission’s project from the perspective of the homeland. Through the use of recurrent metaphors, the Christian faith is associated with light, life and freedom, while ”the heathens” are associated with darkness, weakness and captivity.